Prostate-Specific Antigen Modulates the Expression of Genes Involved in Prostate Tumor Growth - Bindukumar, B (Neoplasia Press Inc., 2005)
Prostate-specific antigen (PSA) is a serine protease that is widely used as a surrogate marker in the early diagnosis and management of prostate cancer. The physiological relevance of tissue PSA levels and their role in prostate tumor growth and metastasis are not known. Free-PSA (f-PSA) was purified to homogeneity from human seminal plasma by column chromatography, eliminating hk2 and all known PSA complexes and retaining its protease activity. Confluent mono-layers of prostate cancer cell lines, PC-3M and LNCaP, were treated with f-PSA in a series of in vitro experiments to determine the changes in expression of various genes that are known to regulate tumor growth and metastasis. Gene array, quantitative polymerase chain reaction (QPCR), and enzyme-linked immunosorbent assay (ELISA) results show significant changes in the expression of various cancer-related genes in PC-3M and LNCaP cells treated with f-PSA. In a gene array analysis of PC-3M cells treated with 10 µM f-PSA, 136 genes were upregulated and 137 genes were downregulated. In LNCaP cells treated with an identical concentration of f-PSA, a total of 793 genes was regulated. QPCR analysis reveals that the genes for urokinase-type plasminogen activator (uPA), VEGF, and Pim-1 oncogene, known to promote tumor growth, were significantly downregulated, whereas IFN-γ, known to be a tumor-suppressor gene, was significantly upregulated in f-PSA-treated PC-3M cells. The effect of f-PSA on VEGF and IFN-γ gene expression and on protein release in PC-3M cells was distinctly dose-dependent. In vivo studies showed a significant reduction (P = .03) in tumor load when f-PSA was administered in the tumor vicinity of PC-3M tumor-bearing BALB/c nude mice. Our data support the hypothesis that f-PSA plays a significant role in prostate tumor growth by regulating various proangiogenic and antiangiogenic growth factors.